Effects of Dietary Nano-Curcumin Supplementation on Growth Performance, Glucose Metabolism, and Endoplasmic Reticulum Stress in Juvenile Largemouth Bass, Micropterus salmoides - Bao, Xiaoxue; Chen, Mingshi; Yue, Yuhua; Liu, Hua; Yang, Ying; Yu, Hui; Yu, Yingying; Duan, Ning (Frontiers in Marine Science, 2022)
This study evaluated the effects of nano-curcumin on growth performance, mucosal immunity, antioxidant response, glucose metabolism, and endoplasmic reticulum stress in largemouth bass. Three groups (three replicates/group) of 270 fish with the mean body weight of 7.00 ± 0.02 g were fed with diets containing 0% (control), 0.1%, and 0.2% nano-curcumin for 60 days. The results showed that dietary supplementation of nano-curcumin had no significant effects on the growth performance, body composition, lysozyme (LYZ), and alkaline phosphatase (AKP) in skin mucus, superoxide dismutase (SOD), and catalase (CAT) activity in serum of largemouth bass. However, dietary supplementation with 0.2% nano-curcumin significantly increased peroxidase (POD) activity in skin mucus and decreased the serum MDA activity compared with the control group. Moreover, dietary supplementation of 0.2% nano-curcumin significantly decreased the levels of serum glucose and liver glycogen, which may be mainly related to the increased gene expression of glucose transporter 2 (GLUT2), glucokinase (GK), phosphofructokinase (PFK), and pyruvate kinase (PK). At the same time, the hepatic gene expression of glucose-regulated protein78 (GRP78), activating transcription factor6 (ATF6), inositol-requiring enzyme 1 (IRE), and eukaryotic initiation factor 2α (eIF2α) in the 0.2% nano-curcumin group were rapidly suppressed, indicating that adding 0.2% nano-curcumin to the diet can alleviate endoplasmic reticulum stress (ERS) in fish. In conclusion, diets supplemented with 0.2% nano-curcumin effectively improved mucosal immunity, antioxidant properties, and glucose metabolism and alleviated ERS induced by long-term carbohydrate intake in largemouth bass.